Notes for a future research on the history of the internship in medicine in Colombia during the 20th century. First part: International background:Europe and North America (19th and 20th centuries) (2019)
This article presents the results of the first part of a study about the development of the internship in Colombian medical education. This first part offers a historical-chronological overview of the birth and development of the “internship” in European and North American medical practice, covering the period of time that begins with its appearance during Napoleo-nian government in France during the 19 th century, and its transformation with the model proposed during the flexnerian reform in the United States at the beginning of the 20 th century, as a starting point for the understanding of the Colombian case. © 2019, Universidad de Antioquia. All rights reserved.